Simulasi Perencanaan Sistem Pembangkit PV dan Bayu Menggunakan Software Homer di Desa Keruak, Kabupaten Lombok Timur - Seftian Aditya Maulana; Ahmad Riki Baihaki; Muhammad Nanang Indrajaya Saputra; Agung Budi Muljono; I Ketut Perdana Putra (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2023)
Human energy needs continue to increase along with an increasingly advanced level of life. Energy can be divided into two categories, namely renewable energy and non-renewable energy. Renewable energy is obtained from unlimited natural resources and will never run out even if it is used continuously. Meanwhile, non-renewable energy is formed from fossil earth which takes millions of years. In contrast to renewable energy, non-renewable energy has a very limited amount and will run out if it continues to be used. In the future, renewable energy will play a very important role in meeting the energy needs of everyday living things. This is caused by the use of fossil fuels as a non-renewable energy source which has long been used by conventional power plants and increasingly sucks up non-renewable energy reserves. Therefore, one solution to overcome this problem is to utilize renewable energy, such as solar and wind energy. The purpose of planning this system is to know the importance of alternative energy in the supply of electrical energy for the community. This research is a simulation based on secondary data from the 2019 East Lombok Regency BPS and uses the Homer Pro software. The simulation results using this software show that the combined on-grid hybrid power plant has a COE value of Rp. 316.74/kWh (PLN) to Rp. 1.352/kWh (hybrid on grid). In this study, the optimization obtained with Homer is using wind power plants and solar panels.